The ankle-brachial index value in patients with purulent-necrotic complications of diabetic foot syndrome - B. O. Matviychuk; V. S. Zaremba; N. R. Fedchyshyn; O. P. Tsymbala (Сучасні медичні технології)
Diabetes and predetermined him heavy purulent-necrotic complications is actual problem medicine today’s. It is proved that patients with diabetes have big risk to development of heart-vessel disease due to the development of atherosclerosis. Standard of diagnosis peripheral arterial disease of lower limb is finding ankle-brachia index (ABI). This method is good at definition of degree of arterial occlusion.